AN ANALYSIS OF BOOK LENDING PRACTICES BASED ON THE ARIYAH CONTRACT AT THE LIBRARY OF THE FACULTY OF ISLAMIC ECONOMICS AND BUSINESS, UIN RADEN FATAH PALEMBANG - Ulil Amri; Yolanda Farista; Yurda Indari (CV. Cendekiawan Muda Sriwijaya, 2025)
This study aims to analyze the practice of book lending at the Library of the Faculty of Islamic Economics and Business (FEBI), UIN Raden Fatah Palembang, from the perspective of the ariyah contract in Islamic law. The ariyah contract is a type of non-commercial lending transaction, in which the lender grants the right to benefit from an item to another party without expecting any compensation, and with the obligation to return the item in its original condition. In the context of a library, this contract is relevant as a fiqh-based foundation for book lending services, which are generally provided free of charge. This research employs a qualitative descriptive approach using a case study method. Data collection techniques include direct observation, in-depth interviews with librarians and library users, and document analysis related to the library’s lending system and regulations. The findings indicate that the book lending system implemented at the FEBI Library substantially reflects the principles of the ariyah contract. Library users are granted the right to benefit from books free of charge for a specified period, with the obligation to return them in good condition. There are no commercial elements or economic gains obtained by the library from this service. This practice not only aligns with sharia principles but also reinforces the values of ta’awun (mutual assistance), public benefit (maslahah), and equity in access to knowledge.